THE ECONOMIC IMPACT OF DIGITAL CURRENCY AND BLOCKCHAIN ON INTERNATIONAL ECONOMICS: POTENTIAL BENEFITS AND RISKS FOR GLOBAL FINANCIAL SYSTEMS - Vasilis Pappas (Modern American Journals, 2025)
The advent of digital currencies and blockchain technology has sparked a profound transformation in the global financial landscape. These technologies offer unprecedented opportunities for enhancing financial inclusion, reducing transaction costs, and streamlining cross-border payments. However, they also present significant risks related to regulatory uncertainty, cybersecurity threats, and potential disruption of existing financial systems. This paper explores the economic impact of digital currencies and blockchain on international economics, focusing on their potential benefits and risks for global financial systems. Through an in-depth analysis, the paper discusses how these technologies can influence international trade, monetary policies, capital flows, and the global banking system. Additionally, the paper presents case studies of countries and organizations that are pioneering these technologies, offering insights into both the challenges and opportunities they present. Ultimately, the research provides policy recommendations for mitigating risks while harnessing the economic potential of digital currencies and blockchain.
Keywords: Digital Currency, Blockchain Technology, International Economics, Global Financial Systems, Economic Impact, Financial Inclusion, Cryptocurrency, Cross-Border Payments, Monetary Policy, Risk Management